Expanding Research Capacity in Sub-Saharan Africa Through Informatics, Bioinformatics, and Data Science Training Programs in Mali - Shaffer, Jeffrey G.; Mather, Frances J.; Wele, Mamadou; Li, Jian; Tangara, Cheick Oumar; Kassogue, Yaya; Srivastav, Sudesh K.; Thiero, Oumar; Diakite, Mahamadou; Sangare, Modibo; Dabitao, Djeneba; Toure, Mahamoudou; et al. (Frontiers in Genetics, 2019)
Bioinformatics and data science research have boundless potential across Africa due to its high levels of genetic diversity and disproportionate burden of infectious diseases, including malaria, tuberculosis, HIV and AIDS, Ebola virus disease, and Lassa fever. This work lays out an incremental approach for reaching underserved countries in bioinformatics and data science research through a progression of capacity building, training, and research efforts. Two global health informatics training programs sponsored by the Fogarty International Center (FIC) were carried out at the University of Sciences, Techniques and Technologies of Bamako, Mali (USTTB) between 1999 and 2011. Together with capacity building efforts through the West Africa International Centers of Excellence in Malaria Research (ICEMR), this progress laid the groundwork for a bioinformatics and data science training program launched at USTTB as part of the Human Heredity and Health in Africa (H3Africa) initiative. Prior to the global health informatics training, its trainees published first or second authorship and third or higher authorship manuscripts at rates of 0.40 and 0.10 per year, respectively. Following the training, these rates increased to 0.70 and 1.23 per year, respectively, which was a statistically significant increase (p < 0.001). The bioinformatics and data science training program at USTTB commenced in 2017 focusing on student, faculty, and curriculum tiers of enhancement. The program’s sustainable measures included institutional support for core elements, university tuition and fees, resource sharing and coordination with local research projects and companion training programs, increased student and faculty publication rates, and increased research proposal submissions. Challenges reliance of high-speed bandwidth availability on short-term funding, lack of a discounted software portal for basic software applications, protracted application processes for United States visas, lack of industry job positions, and low publication rates in the areas of bioinformatics and data science. Long-term, incremental processes are necessary for engaging historically underserved countries in bioinformatics and data science research. The multi-tiered enhancement approach laid out here provides a platform for generating bioinformatics and data science technicians, teachers, researchers, and program managers. Increased literature on bioinformatics and data science training approaches and progress is needed to provide a framework for establishing benchmarks on the topics.